Restricted dominant unanimity and social discounting - Bach Dong Xuan; Xiangyu Qu (Bielefeld University, Center for Mathematical Economics (IMW), 2024)
This paper addresses the intricate challenge of establishing social discount rates across far-reaching generations, particularly in the face of divergent social viewpoints. We introduce several principles related to Dominant Unanimity, which enable non-dictatorial social discounting, and we characterize different ranges of social discount factors based on individual one-period discount factors. Our findings suggest that societies adhering to these principles exhibit varying degrees of patience and different ranges of social discounting. This approach provides theoretical pathways to enhance the consideration of distant future welfare, particularly in the context of long-term economic activities and policies.
urn:nbn:de:0070-pub-29942140
Keywords: 330; Soziale Diskontrate; Abstimmungsregel; Soziale Wohlfahrtsfunktion; Theorie